2017
DOI: 10.1007/jhep09(2017)064
|View full text |Cite
|
Sign up to set email alerts
|

How light a higgsino or a wino dark matter can become in a compressed scenario of MSSM

Abstract: Higgsinos and Wino have strong motivations for being Dark Matter (DM) candidates in supersymmetry, but their annihilation cross sections are quite large. For thermal generation and a single component DM setup the higgsinos or wino may have masses of around 1 or 2-3 TeV respectively. For such DM candidates, a small amount of slepton coannihilation may decrease the effective DM annihilation cross section. This, in turn reduces the lower limit of the relic density satisfied DM mass by more than 50%. Almost a simi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 187 publications
(220 reference statements)
0
24
0
Order By: Relevance
“…The three relevant DM annihilation processes in the early Universe in this context are efficient annihilation of Higgsino DM (potentially also involving coannihilation with similar-mass Higgsino charginos and next-to-lightest neutralinos) or wino DM (potentially involving co-annihilation with similar-mass wino lightest charginos), or resonant annihilation of binos via the SM Higgs or Z boson. Whilst all of these processes have been shown to be effective in the relevant mass range in recent studies [88,157,158], the detailed mixture of the LSP plays a significant role in determining whether the resulting relic density of DM is equal to the full cosmological abundance, or some fraction of it. At a mass of a few tens or hundreds of GeV, pure winos and Higgsinos annihilate too efficiently to produce the full relic density.…”
Section: Implications For Dark Mattermentioning
confidence: 99%
“…The three relevant DM annihilation processes in the early Universe in this context are efficient annihilation of Higgsino DM (potentially also involving coannihilation with similar-mass Higgsino charginos and next-to-lightest neutralinos) or wino DM (potentially involving co-annihilation with similar-mass wino lightest charginos), or resonant annihilation of binos via the SM Higgs or Z boson. Whilst all of these processes have been shown to be effective in the relevant mass range in recent studies [88,157,158], the detailed mixture of the LSP plays a significant role in determining whether the resulting relic density of DM is equal to the full cosmological abundance, or some fraction of it. At a mass of a few tens or hundreds of GeV, pure winos and Higgsinos annihilate too efficiently to produce the full relic density.…”
Section: Implications For Dark Mattermentioning
confidence: 99%
“…In ref. [42], authors have shown that this upper limit for higgsino DM mass can be relaxed if a small amount of slepton co-annihilation is present. Note that in our model such a co-annihilation cannot occur as sleptons are much heavier than the LSP.…”
Section: Clhhs ( B − W ) Modelmentioning
confidence: 99%
“…One can note that LEP also provides limits for the lightest neutralino, but they can be evaded in specific cases and since our analysis is focussed on dark matter and the lightest neutralino, we prefer not to apply it. The neutralino mass will nevertheless be constrained by the light Higgs signal strength measurements, which can lead to stronger limits than LEP [121][122][123][124][125][126]. Table 4.…”
Section: Lep and Tevatron Constraintsmentioning
confidence: 99%
“…In particular, the diphoton channel favours heavy charginos, stops and charged Higgs bosons [121,122,[206][207][208]. In addition, light Higgs decays into supersymmetric particles are rather limited [121,[123][124][125][126]. These important limits provide strong constraints in the (µ, M 2 ) parameter plane.…”
Section: Collider and Dark Matter Constraintsmentioning
confidence: 99%